Longitudinal changes in MR T1ρ/T2 signal of meniscus and its association with cartilage T1p/T2 in ACL-injured patients - Knox, J. (Osteoarthritis Cartilage, 2018)
OBJECTIVE: To evaluate the longitudinal changes in meniscal T1ρ/T2 signal post-reconstruction in patients with acute anterior cruciate ligament (ACL) injury and to investigate the association with T1ρ/T2 signal in articular knee cartilage. METHOD: In this prospective study, knees of 37 patients with ACL-injury and reconstruction in addition to 13 healthy controls were scanned using magnetic resonance imaging (MRI) T1ρ/T2 mapping. Quantitative analysis of the meniscus was performed in the anterior/posterior horns of lateral/medial meniscus fourteen sub-compartments of cartilage spanning the medial/lateral area of the tibia and femoral condyles. Meniscus T1ρ/T2 signals were compared between injured, contralateral and control knees at baseline, 6-months, 1-year and 2-years using t-tests for cross-sectional comparisons and a mixed model for longitudinal comparisons. Pearson-partial correlations between meniscal and cartilage T1ρ/T2 were evaluated. RESULTS: There was a significant decrease of T1ρ/T2 signal in the posterior horn of lateral meniscus (PHLAT) of injured knees during a 2-year period. In the posterior horn of medial meniscus (PHMED), T1ρ/T2 signal of injured knees was significantly elevated at all time points post-reconstruction compared to contralateral and control knees. Within injured knees, PHMED T1ρ/T2 signal showed significant positive correlations with medial tibia (MT) cartilage T1ρ/T2 signal at all time points. CONCLUSION: A significant decrease in PHLAT T1ρ/T2 signal by 2-years suggests potential tissue recovery after ACL-injury. Elevated T1ρ/T2 signal in the PHMED of injured knees at 2-years correlating with knee cartilage T1ρ/T2 signal elevations suggests involvement of the PHMED in subacute cartilage degeneration after ACL-injury and reconstruction.